Establishment of a xenograft model to explore the mechanism of bone destruction by human oral cancers and its application to analysis of role of RANKL. (13th October 2015) - Tohyama, Rei; Kayamori, Kou; Sato, Kiyoshi; Hamagaki, Miwako; Sakamoto, Kei; Yasuda, Hisataka; Yamaguchi, Akira
Abstract : Background: The molecular mechanism underlying bone invasion caused by oral squamous cell carcinoma (OSCC) is not well understood. To elucidate the molecular mechanism, the development of more suitable xenograft models mimicking human mandibular bone destruction by OSCC has been required. Materials and methods: Human OSCC cell lines, HSC3, HSC3‐C1, and HSC3‐R2, were injected in the periosteal region of the mandible in athymic mice, and the bone destruction was analyzed. Receptor activators of nuclear factor κ‐B ligand (RANKL) mRNA and protein expression levels were measured in the OSCC cell lines. Antibody that specifically neutralizes mouse RANKL and human RANKL, respectively, was injected into HSC3‐cell‐transplanted mice. Results: Transplantation of HSC3 cells induced mandibular bone destruction. Histological examination revealed numerous osteoclasts on the bone destruction surface. Fibroblastic cell intervention between the cancer nests and resorbing bone surface was observed in a similar fashion to those observed in human OSCC cases. The number of osteoclasts and fibroblasts was significantly correlated. Bone destruction induced by the transplantation of HSC3 cells was reduced by injection of an antibody that specifically neutralizes mouse RANKL. Transplantation of HSC3‐R2 cells, which overexpresses RANKL, induced advanced bone destruction compared to that of HSC3‐C1 cells, which only overexpress the empty vector. Conclusions: We established a useful xenograft model for investigating the molecular mechanism underlying the bone destruction induced by OSCC in the jaw. This model will be used to investigate the precise roles of several cytokines synthesized by both cancer cells and fibroblastic cells in OSCC‐associated bone destruction in the jaw.